Mitochondrial phylogeny of fusilier fishes (family Caesionidae) from the Laccadive archipelago reveals a new species and two new records from the Central Indian Ocean - Chinmay Kar; Puthiyara Chetta Mariyambi; Rajeev Raghavan; Sivanpillai Sureshkumar (Journal of Fish Biology, 2023)
Fusiliers of the family Caesionidae comprise a group of Indo‐Pacific reef fishes important in the live bait and artisanal fisheries in many parts of its range, particularly in the Indian Ocean region. Using newly generated mitochondrial COI sequences of 10 species of caesionid fishes from the Laccadive archipelago, we carried out a molecular phylogenetic analysis, which has helped improve our understanding of the diversity, distribution, and systematics of this poorly known group of fishes. The two speciose genera within Caesionidae, Caesio and Pterocaesio, were revealed to be paraphyletic, and as a result, four names earlier considered as subgenera within Caesionidae ( Flavicaesio , Odontonectes , Pisinnicaesio , and Squamosicaesio ) were elevated to the status of distinct genera. We also discovered the presence of a new lineage in the Central Indian Ocean, sister to Caesio caerulaurea and Caesio xanthalytos , but distinct from both in several morphological characters and a genetic distance of between 2% and 3% in the mitochondrial COI gene. We describe this lineage as Caesio idreesi , a new species, with a distribution spanning the Laccadive Sea and the Bay of Bengal. Our genetic data also helped confirm the first confirmed records of two species, Pisinnicaesio digramma and Squamosicaesio randalli , from the Central Indian Ocean, and a new distribution record for C. xanthalytos in the Laccadive Sea. Combined, these results have helped bridge key biodiversity knowledge gaps of the family Caesionidae and form an excellent baseline for further investigations on their taxonomy, systematics, and life history.